TINJAUAN YURIDIS PUTUSAN PENGADILAN NEGERI PEKANBARU NOMOR 109/PDT.SUS-PARPOL/2022/PNPBR TENTANG GUGATAN PELAKSANAAN MUSYAWARAH DAERAH DEWAN PIMPINAN DAERAH PARTAI DEMOKRAT PROVINSI RIAU - Salsabila Firdaus; Dessy Artina; Zainul Akmal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The problem of internal conflicts of political parties that occur in the management ofthe democratic party in Riau province. In 2021. This conflict is seen as a conflict over powerand leadership within the democratic party in Riau Province.In this conflict the agitators areAsri Auzar and friends who are legitimate administrators of the Regional Leadership Council(DPD). In his lawsuit, the plaintiff explained the beginning of problems that occurred in themanagement of the Democratic Party.This research is a researcher of normative law. This is based on literature researchthat takes quotations from reading books, or supporting books that have something to do withthe problem to be studied. This study used Secondary data sources consisting of primary,secondary, and tertiary book materials. This study also used qualitative data analysis andproduced Descriptive data.From the results of the research and discussion conducted, there are severalconclusions obtained, namely: first, the case of political party settlement to the district courtis Article 33 paragraph (1) of Law Number 2 of 2011 which reads,